Growing New Zealand Research Capability Using Degree-Based Education: a Commentary After 20 Years of Massage Therapy Graduates - Smith, Joanna; Smith, Donna (International Journal of Therapeutic Massage & Bodywork, 2023)
As massage therapy educators, we started with a desire to cement a place for massage therapy as a legitimate and viable health service. A bachelor degree, underpinned by research-informed education, was the selected mode. In December 2023, our 20th cohort of bachelor degree students will graduate. This commentary describes and reflects on progress towards developing research capability, and en-gagement in and promotion of massage therapy research to learners and practitio-ners of massage therapy in New Zealand.